GLOBAL CORPORATIONS: THE POWER AND IMPACT ONTHE WORLD ECONOMY - Мирясов, Ю. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The articleanalyzes the roleof global corporationsin world development, the issues related to theeconomic powerof big business.The estimation ofthe degree of stabilityand thesize of the firm, which determine thepotential of itseconomic power has been done